Pengaruh narsisme dan job stressor terhadap workplace deviance dan kinerja karyawan (studi pada karyawan bank panin cabang malang) - Dr. Siwi Dyah Ratnasari, SE. MM.; Dr. Rina Rahmawati, SE. MM. (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2021)
The purpose of this study is to determine: 1). The significant effect of narcissism on employee performance, 2). The significant effect of on Workplace Deviance, 3). The significant effect of Job Stressor on Workplace Deviance, 4). Significant influence of Job Stressor on Employee Performance, 5. Significant influence of Workplace Deviance on Employee Performance.The research approach used in this research is quantitative. This type of research is explanatory with the method of collecting data through surveys using a questionnaire. The study population was 52 employees of Bank Panin Branch Malang. The research sample is the same as the total population (saturated sample) The data is analyzed using Path Analysis.The results showed that: 1) Narcissism has a significant effect on employee performance, 2). Narcissism has a significant negative effect on Workplace Deviance, 3). Stres Kerja has a significant negative effect on Workplace Deviance, 4). Stres Kerja has a significant positive effect on Employee Performance, 5). Workplace Deviance has a significant negative effect on Employee Performance.The implication of this research is that the employee's narcissism can improve individual performance. Meanwhile, an increase in Job Stressor within a certain limit has an impact on increasing Employee Performance and decreasing Workplace Deviance